2020
DOI: 10.33069/cim.2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of Heart Rate Assessed by Wearable Devices Tends to Correlate with the Circadian Rhythm of Salivary Cortisol Concentration in Healthy Young Adults

Abstract: The objective of this study was to determine whether the circadian rhythm of heart rate or step count using wearable devices was related to that of the salivary cortisol levels and to test the possibility that the data from wearable devices could be used as an indicator of circadian rhythm misalignment, which is emerging as a cause of insomnia and mood disorders. Methods: The heart rate and step count were continuously measured in 12 healthy young adults using wearable wrist devices for 5 days, and saliva was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Two recent techniques have been developed which now allow researchers to supplement these typical intensive experiments through mobile assessment of circadian rhythms using wearables (5,6). Wearables typically collect data on wrist movement (actigraphy) and heart rate, each of which can separately be used to estimate various outputs of the circadian clock in the body (5)(6)(7)(8)(9)(10)(11). Using mathematical models and activity measurements collected by the Apple Watch, Huang et al recently showed that DLMO can be predicted to within ∼1 h in non-shift workers (5), which is much more accurate (in terms of mean absolute error between a laboratory DLMO measurement and predicted phase) than cosinor analysis of ambulatory circadian rest activity [the average difference between in laboratory DLMO and the acrophase from cosinor analysis of rest-activity cycle is 4.47 and 4.6 h from Huang et al (5) and Woelders et al (12), respectively].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent techniques have been developed which now allow researchers to supplement these typical intensive experiments through mobile assessment of circadian rhythms using wearables (5,6). Wearables typically collect data on wrist movement (actigraphy) and heart rate, each of which can separately be used to estimate various outputs of the circadian clock in the body (5)(6)(7)(8)(9)(10)(11). Using mathematical models and activity measurements collected by the Apple Watch, Huang et al recently showed that DLMO can be predicted to within ∼1 h in non-shift workers (5), which is much more accurate (in terms of mean absolute error between a laboratory DLMO measurement and predicted phase) than cosinor analysis of ambulatory circadian rest activity [the average difference between in laboratory DLMO and the acrophase from cosinor analysis of rest-activity cycle is 4.47 and 4.6 h from Huang et al (5) and Woelders et al (12), respectively].…”
Section: Introductionmentioning
confidence: 99%
“…Second, wearable device data do not guarantee accurate measurement values. Therefore, the wearable data may contain errors before processing . For example, wearable devices tend to be underestimated in a controlled environment and overestimated in a free environment .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the wearable data may contain errors before processing. 51 For example, wearable devices tend to be underestimated in a controlled environment and overestimated in a free environment. 52 Third, the diagnosis of mental disorders should be multifaceted based on expert knowledge and clinical experience.…”
Section: Limitationsmentioning
confidence: 99%
“…Throughout the program, the heart rate was automatically monitored every 5 min using a Mi Band 5 (Xiaomi, China) [ 25 ]. The measured heart rate data were analyzed using a cosine wave function, and the best-fitting model was determined using the least squares regression method [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The measured heart rate data were analyzed using a cosine wave function, and the best-fitting model was determined using the least squares regression method [ 26 ]. Using MATLAB software (MathWorks, USA), we extracted three variables reflecting circadian rhythms: amplitude, mesor, and acrophase [ 25 ].…”
Section: Methodsmentioning
confidence: 99%